THE FEATURES OF POST-GRADUATE DENTAL TRAINING AT THE DEPARTMENT OF POSTGRADUATE EDUCATION OF DENTISTS OF THE UKRAINIAN MEDICAL STOMATOLOGICAL ACADEMY - K. Udaltsova-Hrodzynska; O. Pisarenko (Ukrainian Medical Stomatological Academy, 2018)
According to the requirements, the postgraduate education departments for dentists should be the first to adjust their programs and equipment to technological progress in the branch. During the last two decades the department solved issues of optimal implementation of each technology in the educational process. The object of the paper was the analysis of organization of practical dental training for residency/intern at the Department of Postgraduate Education for Dentists of the "UMSA". At the moment of establishing the Department the features of practical dental training included the maintenance of organized and decreed groups of population by the advanced principle of dispanserization, and also provided physical therapy in dentistry. The examination and rehabilitation of organized groups such as students of the medical school, medical college, participants and "children" of the Second World War, is the priority direction of dental care provision by residency/interns, lead by teachers up to this day. Since the beginning of the photopolymers (or light-activated resin) era in dentistry, a phantom course in restorative dentistry has been introduced in the form of a master class, the achievement of which now is a competition among dental residency/interns for the best restoring front teeth, entitled "The Road to the World of Excellence". Technologies in periodontology are required by trained specialists to improve results of periodontal treatment, which was reflected in programs of the Department and results as organization in 2009 the periodontology course supplemented with master class in Gracey curettes using. In 2007, the Department reviewed the curricula on endodontics standards and organized a phantom course with purpose to profess the method of lateral condensation. During the past 5 years, the course has been converted into a video for demonstration in larger groups to dental residency/interns with phantom equipment such as Endo training blocs, manual endodontic instruments that are close to machine driven ones. The close interaction of dentistry with oncology is realized by the creation of a regional scientific and practical Center for oral mucosal diseases in Poltava, which is a medical institution of the "UMSA", and has the main goal of preventing cancer and precancerous diseases. Professor of the Department, Skrypnikova T.P. is a member of methodical council of Center and she organizes demonstrative consultations for residency/interns which are directly involved in work with patients and treat them according to clinical pathway. Conclusions. 1. Analysis of dental practical training organization reflects the development of new technologies in dentistry, with a little delay. Organization of master classes, video demonstrations, phantom courses and the involvement of private offices as clinical bases of the Department provides opportunity for optimal acquaintance with or mastering over the modern technologies in dentistry, overcomes disadvantages of state financing, allows to set effective practical training and to reduce tedious of training.